Impaired mental rotation in benign paroxysmal positional vertigo and acute vestibular neuritis - Candidi, Matteo; Micarelli, Alessandro; Viziano, Andrea; Aglioti, Salvatore M.; Minio Paluello, Ilaria; Alessandrini, Marco (Frontiers in Human Neuroscience, 2013)
Vestibular processing is fundamental to our sense of orientation in space which is a core aspect of the representation of the self. Vestibular information is processed in a large subcortical-cortical neural network. Tasks requiring mental rotations of human bodies in space are known to activate neural regions within this network suggesting that vestibular processing is involved in the control of mental rotation. We studied whether mental rotation is impaired in patients suffering from two different forms of unilateral vestibular disorders (Vestibular Neuritis – VN- and Benign Paroxysmal positional Vertigo – BPPV) with respect to healthy matched controls (C). We used two mental rotation tasks in which participants were required to: i) mentally rotate their own body in space (egocentric rotation) thus using vestibular processing to a large extent and ii) mentally rotate human figures (allocentric rotation) thus using own body representations to a smaller degree. Reaction times and accuracy of responses showed that VN and BPPV patients were impaired in both tasks with respect to C. Significantly, the pattern of results was similar in the three groups suggesting that patients were actually performing the mental rotation without using a different strategy from the control individuals. These results show that dysfunctional vestibular inflow impairs mental rotation of both own body and human figures suggesting that unilateral acute disorders of the peripheral vestibular input massively affect the cerebral processes underlying mental rotations.